Revitalisasi Pembelajaran Sejarah Kebudayaan Islam Berbasis Konstruktivisme di Museum Provinsi Sulawesi Utara - Gina Nurvina Darise; Rahmawaty Alkatiri; Syamsul Bahri Mamonto (Muróbbî: Jurnal Ilmu Pendidikan, 2026)
This study aims to describe the implementation of constructivism-based Islamic Cultural History learning through the utilization of the North Sulawesi Provincial Museum as a learning laboratory. A descriptive qualitative approach was employed. Data analysis involved data reduction, data display, and conclusion drawing through source triangulation. The findings indicate that museum-based learning creates interactive and contextual learning experiences, enabling students to construct their own understanding through direct interaction with Islamic historical artifacts, particularly the legacies of Imam Bonjol and Kyai Modjo. This learning activity enhances students’ critical and analytical thinking skills as well as their cultural awareness of Islamic civilization in North Sulawesi. In conclusion, the constructivist approach in Islamic Cultural History learning is able to revitalize the learning process, making it more meaningful and relevant to the demands of 21st-century education.